Internalization Of The Values Of The Qur'an And Hadith In The Daily Life Of Students At School (A Study of the Islamic Character of Students of MI Muhammadiyah Tambaksari Blora) - Munawar, Mohamad (JURNAL PEDAGOGY, 2025)
Education plays a vital role in shaping the character of the young generation as the successors of the nation. The main problem raised in this study is the less than optimal internalization of the values of the Qur'an and Hadith in the formal education process, which has an impact on the weak moral character of students. In fact, Islamic education should not only emphasize intellectual aspects, but also spiritual and moral. This study aims to explore the implementation of the values of the Qur'an and Hadith in the formation of student character at MI Muhammadiyah Tambaksari Blora. This study uses a qualitative approach with a field study method, involving observation, in- depth interviews, and documentation as data collection techniques. The results of the study show that schools consistently integrate the values of the Qur'an and Hadith through Qur'an learning activities, congregational prayers, and student moral formation programs. The role of teachers is very significant in guiding students to understand and practice Islamic values in everyday life. Activities such as congregational prayers have proven effective in instilling discipline, responsibility, and a spirit of togetherness. In addition, the application of good morals in social interactions at school encourages the creation of a harmonious environment, mutual respect, and strengthens Islamic broth- erhood. Based on these findings, it can be concluded that the implementation of the values of the Qur'an and Hadith in a structured manner can shape the character of stu- dents who are religious, have noble character, and are responsible. This supports the views of Al-Ghazali and Ibn Sina that Islamic education must include moral, spiritual, and intellectual aspects. This study confirms that education based on Islamic values is still very relevant and urgent in the context of character education in the modern era.